Topology and Scenography Variables in Theatrical Show: Yes Godot as a Model - Ibrahim, Inam Maan (Journal of Tikrit University for Humanities, 2023)
Theatre experiments stem from human history’s social, political, economic, and moral factors. Theatre helps society identify and handle these issues artistically, intellectually, technically, and aesthetically. Additionally, adjacent sciences have contributed to theatre’s development through major revolutions (the First and Second World Wars), industrial revolutions, and technological advancements that helped crystallize scenography in the theatre stage space. The topology or elastic engineering of variables in the matter that does not vary in its own shape, but rather its exterior frameworks, recycles space according to the theatrical show’s intellectual and technical needs. As this research was determined by studying (topology and scenography variables in the theatrical show), the researcher analysed a deliberate theatrical performance by director Anas Abdul Samad at the Rashid Theatre in 2021 under the title yes Godot, which dealt with the impact of place and scenography variables, elastic engineering (topology), and its harmonies with the theatrical space, as well as its effectiveness and operation. The researcher focused on the issue axis that asked what is topology? stenographic variables? how do they affect the theatre’s construction. The researcher tried to answer those aesthetic questions by showing the correlations and harmonies between topology and scenography variables in the formations of show elements and the effectiveness of the theatrical space’s visual image structure through scenography related to the actor’s performance in space and his operations on the rest of the theatrical production elements.